Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Motivasi Serta Dampaknya Terhadap Kinerja Pegawai Pengadilan Negeri Jambi - Firman Syah Noor (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to determine and analyze the description of transformational leadership, organizational culture, motivation and performance, and the relationship between the four variables at the Jambi District Court employees. This study uses descriptive and verificative research methods that aim to describe research variables systematically and in accordance with the facts investigated, as well as knowing the relationship between variables through testing hypotheses. The study sample used as many as 74 employees of the Jambi District Court, The results of the descriptive analysis show that the overall level of transformational leadership quality and organizational culture in the Jambi District Court are at a good level of quality. While for work motivation and employee performance are at a high level of quality. The results of hypothesis testing through path analysis prove that transformational leadership and organizational culture both partially and simultaneously have a significant effect on work motivation and employee performance. For the indirect effects of transformational leadership and organizational culture on employee performance through work motivation, it shows that the application of transformational leadership and good organizational culture can increase employee motivation at a higher level, which indirectly has an impact on improving employee performance. However, on the other hand work motivation partially does not affect employee performance.